2018
DOI: 10.1037/xhp0000433
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus expectation prolongs rather than shortens perceived duration: Evidence from self-generated expectations.

Abstract: Previous studies have suggested that unexpected stimuli are perceived as being longer than expected ones (e.g., the temporal oddball effect). These studies manipulated stimulus expectation mostly via stimulus repetitions and stimulus probabilities. However, these manipulations might affect duration judgments not only through the modulation of stimulus expectation. Therefore, the present study introduces a novel paradigm to isolate the effect of stimulus expectation on perceived duration from repetition and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 52 publications
8
43
1
Order By: Relevance
“…A similar conclusion is urged by recent work from Birngruber et al (2017) , which found that explicit expectations about forthcoming stimuli do indeed serve to expand subjective time. These authors asked people to predict the color or shape of stimuli immediately before they were presented; items that matched the prediction were judged to last longer than those that did not.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…A similar conclusion is urged by recent work from Birngruber et al (2017) , which found that explicit expectations about forthcoming stimuli do indeed serve to expand subjective time. These authors asked people to predict the color or shape of stimuli immediately before they were presented; items that matched the prediction were judged to last longer than those that did not.…”
Section: Introductionsupporting
confidence: 67%
“…Like the results of Matthews (2015) , the current data indicate that the effects of repetition on subjective time are not due to the repeated stimuli being “predicted” or “expected.” Rather, the data suggest that first-order repetition compresses subjective time through some other mechanism, such as low-level sensory adaptation ( Bruno et al, 2010 ; Cai et al, 2015 ), whereas expectation expands subjective duration ( Birngruber et al, 2017 ), perhaps by improving the detection of the stimulus ( Kim and McAuley, 2013 ) or the extraction of information from it ( Matthews, 2015 ).…”
Section: Discussionmentioning
confidence: 96%
“…The fact that perceived duration is affected by the observer’s expectations about stimuli is of particular interest here; how this phenomenon operates is still an open question. There is existing evidence to suggest that fulfilled expectations reduce (Tse et al, 2004; Ulrich et al, 2006; Pariyadath and Eagleman, 2007, 2012; Matthews, 2011; Schindel et al, 2011), do not reduce (van Wassenhove et al, 2008; Cai et al, 2015), or even increase perceived duration of a stimulus (Matthews’, 2015; Matthews and Gheorghiu, 2016; Matthews and Meck, 2016; Schweitzer et al, 2017; Skylark and Gheorghiu, 2017; Birngruber et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a classical temporal oddball task, the duration of an unexpected deviant target stimulus (oddball) is overestimated if it is presented randomly within a train of repetitive stimuli with a constant standard duration (Tse et al, 2004; Pariyadath and Eagleman, 2007, 2012; Schindel et al, 2011; Birngruber et al, 2014). This phenomenon has been termed “time’s subjective expansion” (Tse et al, 2004), “oddball chronostasis” (Lin and Shimojo, 2017), or more usually the “temporal oddball effect” (OE; e.g., Pariyadath and Eagleman, 2007, 2012; Schindel et al, 2011; Birngruber et al, 2014, 2018; Matthews and Gheorghiu, 2016). The OE is a robust perceptual phenomenon that persists regardless of the type of temporal task used (e.g., Tse et al, 2004; Matthews, 2011; Birngruber et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation